Simultaneous fermentation of cellulose and current production with an enriched mixed culture of thermophilic bacteria in a microbial electrolysis cell. Issue 1 (29th May 2017) - Lusk, Bradley G.; Colin, Alexandra; Parameswaran, Prathap; Rittmann, Bruce E.; Torres, Cesar I.
Summary: An enriched mixed culture of thermophilic (60°C) bacteria was assembled for the purpose of using cellulose to produce current in thermophilic microbial electrolysis cells (MECs). Cellulose was fermented into sugars and acids before being consumed by anode‐respiring bacteria (ARB) for current production. Current densities ( j ) were sustained at 6.5 ± 0.2 A m −2 in duplicate reactors with a coulombic efficiency (CE) of 84 ± 0.3%, a coulombic recovery (CR) of 54 ± 11% and without production of CH4 . Low‐scan rate cyclic voltammetry (LSCV) revealed a mid‐point potential ( E ka ) of −0.17 V versus SHE. Pyrosequencing analysis of the V4 hypervariable region of 16S rDNA and scanning electron microscopy present an enriched thermophilic microbial community consisting mainly of the phylum Firmicutes with the Thermoanaerobacter (46 ± 13%) and Thermincola (28 ± 14%) genera occupying the biofilm anode in high relative abundance and Tepidmicrobium (38 ± 6%) and Moorella (11 ± 8%) genera present in high relative abundance in the bulk medium. The Thermoanaerobacter (15 ± 16%) and Brevibacillus (21 ± 30%) genera were also present in the bulk medium; however, their relative abundance varied by reactor. This study indicates that thermophilic consortia can obtain high CE and CR, while sustaining high current densities from cellulose in MECs. Abstract : An enriched mixed culture of thermophilic (60°C) bacteria was assembled for the purpose of using cellulose to produce current in thermophilic microbial electrolysis cells (MECs). Cellulose was fermented into sugars and acids before being consumed by anode respiring bacteria (ARB) for current production. Current densities ( j ) were sustained at 6.5 ± 0.2 A m −2 in duplicate reactors with a Coulombic efficiency (CE) of 84 ± 0.3%, a Coulombic recovery (CR) of 54 ± 11%, and without production of CH4 .